Pengembangan Ekosistem Usaha Wisata Halal Bebas Pungli Berbasis Manajemen Bisnis Syariah di Kawasan Sentul Kabupaten Bogor - Novingky Ferdinand; Sawqi Saad El Hasan; Ermi Herawati; Cecep Suherman; Dedy Darmawan (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
Halal tourism development in Sentul, Bogor, is hindered by illegal levies (pungli) and the lack of halal certification, which damage tourist trust. This community service aims to establish an extortion-free business ecosystem based on Sharia Business Management. Using the Participatory Action Research (PAR) method with four partners, activities included social mapping, participatory planning, and assistance for NIB and halal certification via SIHALAL. Success was evaluated using the Policy Acceptance Model (Vlassenroot et al., 2008). Results show significant transformation: four partners successfully completed the halal certification submission process, and an